(untitled) (Palimpsesto, 2019)
This research proposes a reflection on the testimonies of political prison in the Southern Cone, focusing specifically on its supports, that is, the material form by which they think, construct and disseminate these testimonies as part of the studies on memory. Regarding the above, this area is deepened in the testimonial studies has not considered or addressed and is crucial to understand and work around them from an interdisciplinary approach, as well as conditions both the forms of representation and the self-representation of the testifying subject and its possibilities of circulation and diffusion. For this, an extensive and diversified corpus of testimonial works is addressed, specifically considering Chilean, Argentine and Uruguayan experiences.